2018
DOI: 10.1002/maco.201810566
|View full text |Cite
|
Sign up to set email alerts
|

Dual functions of chloride ions on corrosion behavior of mild steel in CO2 saturated aqueous solutions

Abstract: Corrosion behavior of mild steel in CO2 saturated aqueous solutions at room temperature as a function of concentration of chloride ions was investigated through electrochemical and surface characterizations. In CO2 saturated solutions, mild steel corrodes rapidly with the chloride ions concentration until a peak value around 0.2 mol/L as a result of the adsorption and catalytic dissolution mechanism of chloride ions on Fe matrix. In contrast, the corrosion rate of mild steel is retained at a stable value with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…There is a wealth of research reaching [1,7,8,10,14,15,16,17,18,19] focusing on the influence of 1-5% Cr addition to steels to improve strength, hardenability and CO2 corrosion resistance, with the majority of observations concluding that Cr addition does improve corrosion performance [7,10] . In addition, a number of successful field trials have been reported [14,20] with the use of low Cr alloyed steels.…”
Section: Introductionmentioning
confidence: 99%
“…There is a wealth of research reaching [1,7,8,10,14,15,16,17,18,19] focusing on the influence of 1-5% Cr addition to steels to improve strength, hardenability and CO2 corrosion resistance, with the majority of observations concluding that Cr addition does improve corrosion performance [7,10] . In addition, a number of successful field trials have been reported [14,20] with the use of low Cr alloyed steels.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Cl – in the solutions can absorb preferentially on AZ91D alloy surfaces, which may lead to the formation of surface transient complexes with metal ions, and promote the mass transport of metal ions . On the other hand, the localized adsorption of Cl – on specimen surfaces can enhance the dissolution of oxide films at these sites, thinning of the oxide film until its removal, and active dissolution . At electric current density 5, 10, and 20 mA/cm 2 , the oxide films formed on AZ91D alloy surfaces is partially destroyed by Cl − ions in the initial stage (10 min) of galvanostatic measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In a static system, at 25 °C, Zhang et al showed that corrosion rates significantly increased with increasing NaCl concentration, even when introduced in traces (0.12% w/v), due to increasing both cathodic and anodic current densities. However, this effect diminished as NaCl concentration exceeded 3.5% w/v . Similarly, however, under dynamic conditions, Kanimozhi et al reported that at 1–5% w/v NaCl concentrations, the corrosion rate exhibited an increase as a function of increasing NaCl content.…”
Section: Introductionmentioning
confidence: 97%
“…However, this effect diminished as NaCl concentration exceeded 3.5% w/v. 31 Similarly, however, under dynamic conditions, Kanimozhi et al reported that at 1−5% w/v NaCl concentrations, the corrosion rate exhibited an increase as a function of increasing NaCl content. Nevertheless, with further increasing concentrations, 5−30% w/v, a decrease in corrosion rate was observed.…”
Section: ■ Introductionmentioning
confidence: 98%
See 1 more Smart Citation